Nurturing the Next Generation with the Utilization of Entrepreneurial, Cultural, and Financial Competencies - Khong, Rifin; Kaban, Lila Maria; Alimin, Erina; Meilani, Meilani; Ciptawan, Ciptawan (JPM: Jurnal Pengabdian Masyarakat, 2025)
This article presents a community service initiative conducted by university lecturers and students aimed at nurturing entrepreneurial, cultural, and financial competencies among children in a local orphanage in Medan, Indonesia. A preliminary interview with the orphanage manager showed that the children required intensive engagement and education outside their schools and community. The one-day onsite program involved children, ranging from primary to high school level, through interactive learning modules that included entrepreneurship education, cultural awareness, and financial literacy. Activities such as simulations, group discussions, and games were used to encourage active participation and improve understanding. The results showed increased entrepreneurial motivation by 28%, cultural appreciation by 27%, and basic financial knowledge by 22% among participants. Student facilitators also gained practical experience in community engagement and leadership. Despite time limitations, the program successfully created a positive learning environment and promoted essential life skills for vulnerable youth. Recommendations are to extend the program duration, create age-specific content, and develop long-term mentorship to enhance impact. This initiative underscores the vital role of higher education in community empowerment and sustainable youth development.